Designing a Web-Based Data Management System at BAPPEDA-LITBANG Tambrauw - Nebore, Gloria Roselyn Charity; Maria (SCOPUS ID: 57093633500), Evi (Sistemasi: Jurnal Sistem Informasi, 2024)
BAPPEDA-LITBANG Tambrauw, a regional technical institution in Tambrauw Regency, Southwest Papua, faces challenges in data management related to data integration and access. This condition hampers the planning and decision-making process there. This research aims to design a web-based data management system that can integrate various types of data from multiple sources, making it easier to access and analyze data in the agency. The prototype method was used in developing this system through problem identification, needs analysis, system design, implementation, testing, and improvement and evaluation. The research results show that the proposed web-based data management information system can overcome the challenges of limited data access and lack of data integration and support regional development that is more structured and responsive to community needs. In addition, this system can be a reference for developing systems in other government institutions with similar characteristics and challenges.